Capital Gains Tax Rules, Tax‐loss Trading, and Turn‐of‐the‐year Returns - Poterba, James M.; Weisbenner, Scott J. (Journal of Finance, 2001)
ABSTRACT Changes in the capital gains tax rules facing individual investors do not affect the incentives for “window dressing” by institutional investors, but they can affect the incentives for year‐end tax–induced trading by individual investors. Empirical evidence for the 1963 to 1996 period suggests that when the tax law encouraged taxable investors who accrued losses early in the year to realize their losses before year‐end, the correlation between early year losses and turn‐of‐the‐year returns was weaker than when the law did not provide such an early realization incentive. These findings suggest that tax‐loss trading contributes to turn‐of‐the‐year return patterns.